2014
DOI: 10.1016/j.scitotenv.2014.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish and clean water technology: Assessing soil bioretention as a protective treatment for toxic urban runoff

Abstract: Urban stormwater contains a complex mixture of contaminants that can be acutely toxic to aquatic biota. Green stormwater infrastructure (GSI) is a set of evolving technologies intended to reduce impacts on natural systems by slowing and filtering runoff. The extent to which GSI methods work as intended is usually assessed in terms of water quantity (hydrology) and quality (chemistry). Biological indicators of GSI effectiveness have received less attention, despite an overarching goal of protecting the health o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 44 publications
7
68
0
Order By: Relevance
“…Effects such as increased mortality, decreased escape response, and histological abnormalities were demonstrated in PAH‐exposed Danio rerio (Incardona et al ) and pesticide‐exposed fathead minnows (Beggel et al ). Similar effects as in Incardona et al () and Beggel et al () were observed in urban stormwater‐exposed Hyalella azteca, Danio rerio, Ceriodaphnia dubia, D. magna , and fathead minnows (McQueen et al ; Bartlett et al ; McIntyre et al ; Weston et al ). Stormwater‐exposed fathead minnow larvae also showed delayed hatching, smaller eyes, and reduced cardiac function (Sarma and Nandini ; McIntyre et al ).…”
Section: Introductionsupporting
confidence: 74%
“…Effects such as increased mortality, decreased escape response, and histological abnormalities were demonstrated in PAH‐exposed Danio rerio (Incardona et al ) and pesticide‐exposed fathead minnows (Beggel et al ). Similar effects as in Incardona et al () and Beggel et al () were observed in urban stormwater‐exposed Hyalella azteca, Danio rerio, Ceriodaphnia dubia, D. magna , and fathead minnows (McQueen et al ; Bartlett et al ; McIntyre et al ; Weston et al ). Stormwater‐exposed fathead minnow larvae also showed delayed hatching, smaller eyes, and reduced cardiac function (Sarma and Nandini ; McIntyre et al ).…”
Section: Introductionsupporting
confidence: 74%
“…The average reduction of total suspended solids by all bioswales in the present study was 79%, comparable to the range of 83% to 92% reported by Oregon Department of Environmental Quality . McIntyre et al reported a total suspended solids reduction of 72%. In the present study, PAH concentrations were generally low and were reduced by greater than 98% in all bioswale effluents during the 3 storms.…”
Section: Discussionmentioning
confidence: 99%
“…These include the early life stages of zebrafish (McIntyre et al . ), juvenile coho salmon and their macroinvertebrate prey (McIntyre et al . ), and adult coho spawners (this study).…”
Section: Discussionmentioning
confidence: 99%
“…The PAH profile of urban run‐off is compositionally similar to that of crude oil, particularly for toxic three‐ and four‐ring compounds (McIntyre et al . ). The exception is a lack of dissolved pyrene and fluoranthene in crude oil (Incardona et al .…”
Section: Methodsmentioning
confidence: 97%